2017
DOI: 10.1016/j.jcis.2017.06.071
|View full text |Cite
|
Sign up to set email alerts
|

Spectral induced polarization of Na-montmorillonite dispersions

Abstract: Montmorillonite (Mt) clays have a high specific surface area and surface charge, which confer them remarkable adsorption properties. Nevertheless, their electrochemical and aggregation behavior are not completely elucidated because of the complexity of their microstructural and interfacial properties. In this work, the conductive and dispersive properties of Na-Mt suspensions of weight fractions 0.5-5.2% were investigated for the first time using the spectral induced polarization method. A four-electrode syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 95 publications
2
38
0
Order By: Relevance
“…; Leroy et al . ). Clay minerals usually have a smaller particle diameter than other minerals – typically in the range 0.1–10 µm (e.g.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Leroy et al . ). Clay minerals usually have a smaller particle diameter than other minerals – typically in the range 0.1–10 µm (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…type of ions, concentration, pH, temperature) influences the imaginary and surface conductivity as well Weller et al 2011;Weller, Zhang and Slater 2015b). It is also suggested that the presence of clay minerals may cause an increase in polarization effects, in addition to an increased surface conductivity (Vinegar and Waxman 1984;Weller et al 2015a;Leroy et al 2017). Clay minerals usually have a smaller particle diameter than other minerals -typically in the range 0.1-10 µm (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The anomalous low-frequency dielectric response of charged particles immersed in an electrolyte has been observed in various types of systems, from suspensions of polystyrene latex particles, emulsions of fat particles [1], and suspensions of clay particles [12,13] to complicated rock formations [42]. Often, the explication of this phenomenon begins with the single-particle polarization response, similar to that given in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Rock polarization is also sensitive, to a lesser extent, to the pore size, the presence of clay minerals, and the electrolyte conductivity, especially in the case of sandstones (Binley et al, 2005;Klein & Sill, 1982;Kruschwitz, 2007;Kruschwitz et al, 2010;Leroy et al, 2017;Lesmes & Frye, 2001;Revil & Skold, 2011;Slater & Sandberg, 2000;Weller & Slater, 2012;Weller et al, 2013). Similarly to connected metallic particles, connected clay minerals may also prevent polarization and cause conduction instead.…”
Section: Introductionmentioning
confidence: 99%